High‐speed wire electrical discharge machining to create superhydrophobic surfaces for magnesium alloys with high corrosion and wear resistance. Issue 10 (8th June 2020) - Qiu, Rongxian; Li, Chao; Tong, Wei; Xiong, Dangsheng; Li, Zhongxin; Wu, Zhilin
Abstract: Herein, a superhydrophobic surface of AZ31B magnesium alloy prepared by high‐speed wire electrical discharge machining and modification with stearic acid is reported. The surface morphology and wettability of the superhydrophobic surface were investigated by scanning electron microscopy and optical contact angle measurement, respectively. A uniform micro‐/nanopetal‐like structure was shown within the superhydrophobic surface, resulting in a contact angle of 151 ± 0.5° and a sliding angle of 4 ± 0.5°. Notably, the superhydrophobic surface had better corrosion resistance than the bare magnesium alloy, and its corrosion current density was reduced by nearly one order of magnitude. Under both dry and wet friction conditions, the friction coefficient of the superhydrophobic surface was lower than that of the bare magnesium alloy surface, with a much lower wear loss. In addition, the friction coefficient of the superhydrophobic sample was lower than that of the bare magnesium alloy sample under both the dry and wet friction conditions. Thus, the superhydrophobic sample experienced reduced wear and had a low wear rate. Abstract : The superhydrophobic surface of a AZ31B magnesium alloy prepared by high‐speed wire electrical discharge machining and modification with stearic acid had better corrosion resistance than the bare magnesium alloy. Under both dry and wet friction conditions, the friction coefficient of the superhydrophobic surface was lower than that of the bare magnesium alloy surface, with a much lower wear loss.